Implementasi Metode Fuzzy Logic untuk Mendeteksi Asap Dupa di Pasar Tradisional Bali Berbasis IoT - Arituddiniyah, Ira; Pramartha, Cokorda; Atmaja Darmawan, I Dewa Made Bayu; Surya Rahayuda, I Gede (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana), 2024)
This research employs Fuzzy Logic for incense smoke detection in Bali's traditional markets, supported by IoT. It aims to develop a system for automatic identification, user reminders, and online monitoring. By using Fuzzy Logic, the system assesses smoke concentration, enabling appropriate responses. IoT integration facilitates object connectivity and communication. The outcome is a web platform for smoke monitoring, notifications, and remote device control. This study innovatively merges IoT with local wisdom, offering a valuable contribution.